Five Days azithromycin is more efficient than teo DaysErythromycin for the Treatment of pertussis - D. Moohy Alosy, Baha (Tikrit Journal of Pharmaceutical Sciences, 2023)
Whooping cough (pertussis) is a highly contagious caused by Bordetella pertussis. During the last decade three Bordetella pertussis isolates have been found to be resistant to erythromycin, the azithromycin are used for treatment of pertussis. Sixty Child as 31 (5-day group) and 29 (10-day group) with pertussis in private clinic were evaluated for more efficiency of a 3-day course azithromycin in compares to a 10-day course erythromycin therapy. Treatment outcomes were stand on rates of bacteriological cure. Participants were randomized to receive 5 Days azithromycin (10 mg/kg/d) once a day or 10 Days Erythromycin 40 -30mgkg/ d in 4 divided doses, Bacteriological persistence did not happened for azithromycin ( 0% ) But for erythromycin ( one =3.44 %). Bacteriological failures occurred with azithromycin treatment (one =322%)while in Erythromycin (two ~~ =7.40 %) the estimates of bacterial cure were elevated for azithromyein 96.77% in compares for erythromycin 93.10% the bacterial cure rate time was 16.48 days for azithromycin less than for erythromycin 24.2625 days. The Variance in clinical manifestation duration for azithromycin 36.6 days less than for erythromycin 47.5 days for that our study recommended that 5-day azithromycin is more efficient than 10-day erythromycin in the treatment of pertussis in children.